Intestinal Fatty Acid Binding Protein, a Biomarker of Intestinal Barrier, is Associated with Severity of Psoriasis - Sikora, Mariusz (J Clin Med, 2019)
Alterations of intestinal microbiota play a significant role in the pathogenesis of psoriasis. Dysbiosis may cause disruption of the intestinal barrier, which contributes to immune activation by translocation of microbial antigens and metabolites. Intestinal fatty acid binding protein (I-FABP) serves as a biomarker of enterocyte damage. The aim of this study was to investigate clinical and metabolic factors affecting plasma concentration of I-FABP in patients with psoriasis. Eighty patients with psoriasis and 40 control subjects were enrolled in the study. Serum I-FABP (243.00 (108.88–787.10) vs. 114.38 (51.60–241.60) pg/ml, p < 0.001) and neutrophil to lymphocyte ratio (NLR; 2.59 (1.96–3.09) vs. 1.72 (1.36–47 2.11), p < 0.01) were significantly increased in patients with psoriasis compared to controls. A significant positive correlation was found between I-FABP and body mass index (BMI) (r = 0.82, p < 0.001), Psoriasis Area Severity Index (PASI) (r = 0.78, p < 0.001) and neutrophil to lymphocyte ratio (NLR) (r = 0.24, p < 0.001). Rising quartiles of I-FABP were associated with increasing values of BMI, PASI and NLR. The results of the logistic regression model confirmed an increased risk of higher disease severity with I-FABP concentration – odds ratio 3.34 per 100 pg/mL I-FABP increase. In conclusion, intestinal integrity in patients with psoriasis is affected by obesity, severity of the disease and systemic inflammation. The modulation of gut barrier may represent a new therapeutic approach for psoriasis.